Creation of mechanical respirators in the days of COVID-19 in Brazil: a narrative review (Research, Society and Development, 2020)
The COVID-19 pandemic has presented itself as a major challenge for Brazil, registering more than 134 thousand deaths in five months with more than 4,4 million people infected. Researchers from educational institutions and companies have endeavored to develop alternative mechanical respirators due to their high cost and demand. This study aims to present and analyze initiatives of the scientific community in the development of mechanical respirators in Brazil. It is a narrative review divided into two stages: 1) survey of the models of mechanical respirators developed during the pandemic and 2) holding a discussion forum involving professionals from different academic areas in the Northeast, where themes were highlighted about the impact of COVID- 19 in Brazil, the need and diagnosis for the use of mechanical respirators and criteria of scientific authenticity. Mechanical respirator designs are believed to be relevant not only for the current moment, but also for the post-pandemic.